2012
DOI: 10.1007/s00436-012-2867-0
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of silver nanoparticles synthesized using Pergularia daemia plant latex against Aedes aegypti and Anopheles stephensi and nontarget fish Poecillia reticulata

Abstract: In present study, the bioactivity of latex-producing plant Pergularia daemia as well as synthesized silver nanoparticles (AgNPs) against the larval instars of Aedes aegypti and Anopheles stephensi mosquito larvae was determined. The range of concentrations of plant latex (1,000, 500, 250, 125, 62.25, and 31.25 ppm) and AgNPs (10, 5, 2.5, 1.25, 0.625, and 0.3125 ppm) were prepared. The LC(50) and LC(90) values for first, second, third, and fourth instars of synthesized AgNPs-treated first, second, third, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(51 citation statements)
references
References 23 publications
5
44
0
2
Order By: Relevance
“…In agreement with our results, Pergularia daemia-synthesized AgNPs have been reported as non-toxic against the non-target fish Poecilia reticulata, while they are able to evoke good mortality rates against mosquito vectors Anopheles stephensi and Ae. aegypti (Patil et al 2012; see also Haldar et al 2013;Rawani et al 2013). More recently, Murugan et al (2015a) showed that seaweed-synthesized AgNPs did not negatively impact the predation rates of copepod Mesocyclops longisetus against Cu.…”
Section: Toxicity Against Anopheles Stephensimentioning
confidence: 96%
“…In agreement with our results, Pergularia daemia-synthesized AgNPs have been reported as non-toxic against the non-target fish Poecilia reticulata, while they are able to evoke good mortality rates against mosquito vectors Anopheles stephensi and Ae. aegypti (Patil et al 2012; see also Haldar et al 2013;Rawani et al 2013). More recently, Murugan et al (2015a) showed that seaweed-synthesized AgNPs did not negatively impact the predation rates of copepod Mesocyclops longisetus against Cu.…”
Section: Toxicity Against Anopheles Stephensimentioning
confidence: 96%
“…The larvicidal activity of silver nanoparticles synthesized plant latex has been screened against the nontarget fish Poecilia reticulata (Patil et al 2012). The larvicidal activities of mycosynthesized AgNPs against vectors and responsible for diseases of public health importance have been evaluated (Salunkhe et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…By employing this method, the size distribution of SNPs obtained was smaller when compared to previous reports, viz. 44 to 225 nm using Pergularia daemia plant latex [31] and 71 to 110 nm using mangrove plant Avicennia marina [32].…”
Section: Characterization Of Snpsmentioning
confidence: 99%